Development and verification of a cure-dependent visco-thermo-elastic simulation model for predicting the process-induced surface waviness of continuous fiber reinforced thermosets. (March 2023) - Lorenz, N.; Gröger, B.; Müller-Pabel, M.; Gerritzen, J.; Müller, J.; Wang, A.; Fischer, K.; Gude, M.; Hopmann, Ch.
Process-induced surface waviness effects represent a major concern for series production of high-quality lightweight structures based on fiber reinforced plastics (FRP). This paper suggests a method for the numerical prediction of these effects by using the example of processing glass fiber reinforced plastics (GFRP) in a resin transfer molding (RTM) process. The influence of reaction kinetics, chemical shrinkage and cure-dependent viscoelastic properties of the resin are taken into account. Furthermore, the dependence of surface quality on curing cycle, consolidation pressure, textile architecture and thickness of neat resin layer (NRL) at the part surface are investigated. The work is based on published material data and a visco-thermo-elastic simulation approach which has been previously presented and validated. All numerical results are compared to the surfaces of FRP plates that were manufactured with the corresponding parameter variations. Based on a literature survey, different surface waviness values have been identified for comparison of experimental and numerical results. Satisfactory agreement between experiments and simulations is found. Furthermore, it is shown that the analyzed NRL thickness has no relevant influence on the surface waviness while the curing temperature significantly affects the surface waviness. The role of relaxation-induced change of the surface waviness is highlighted by performing long-term measurements and corresponding time-dependent simulations. It is concluded that relaxation plays a decisive role in the appropriate selection of the subsequent surface finishing process. The suggested simulation approach provides a basis for optimization strategies to improve surface quality and reduce post-processing effort.